Activation of Nucleases, PCD, and Mobilization of Reserves in the Araucaria angustifolia Megagametophyte During Germination - Moyano, Laura; Correa, María D.; Favre, Leonardo C.; Rodríguez, Florencia S.; Maldonado, Sara; López-Fernández, María P. (Frontiers in Plant Science, 2018)
The megagametophyte of mature seeds of Araucaria angustifolia consists of cells with thin walls, one or more nuclei, a central vacuole storing proteins, and a cytoplasm rich in amyloplasts, mitochondria and lipid bodies. In this study, we describe the process of mobilization of reserves and analyzed the dismantling of the tissue during germination, using a range of well-established markers of programmed cell death (PCD), including: morphological changes in nuclei and amyloplasts, DNA degradation, and changes in nuclease profiles. TUNEL reaction and DNA electrophoresis demonstrate that DNA fragmentation in nuclei occurs at early stages of germination, which correlates with induction of specific nucleases. The results of the present study add knowledge on the dismantling of the megagametophyte of genus Araucaria, a storage tissue that stores starch as the main reserve substance, as well as on the PCD pathway, by revealing new insights into the role of nucleases and the expression patterns of putative nuclease genes during germination.